2000
DOI: 10.1002/1521-3951(200011)222:1<133::aid-pssb133>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Defects and the D1 to D4 Optical Bands Detected in Plastically Deformed Si

Abstract: The properties of multi-vacancy and multi-interstitial defects that possess luminescent bands around 1 eV are reviewed. Prominent among these are the hexavacancy and tri-and tetra-self-interstitial defects. It is suggested that the formation of these defects on dislocation cores could lead to the D1 to D4 photoluminescent bands linked to dislocations in Si and SiGe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…According to the literature, some impurity atoms in the dislocation core [205], dislocation jogs [206], segments of dislocations of special types (like Lomer dislocations) appearing due to dislocation reactions, multi-vacancies in the dislocation core [207] are typical examples of the possible origin of the D1 luminescence. When selecting a model it should be taken into account that the D1 band usually dominates the luminescence spectra in samples with a high local dislocation density (see, e.g., Figure 4.13(a)) where dislocations could interact with each other.…”
Section: Dislocation Luminescence: a Tool To Probe Gettering At Dislosupporting
confidence: 54%
“…According to the literature, some impurity atoms in the dislocation core [205], dislocation jogs [206], segments of dislocations of special types (like Lomer dislocations) appearing due to dislocation reactions, multi-vacancies in the dislocation core [207] are typical examples of the possible origin of the D1 luminescence. When selecting a model it should be taken into account that the D1 band usually dominates the luminescence spectra in samples with a high local dislocation density (see, e.g., Figure 4.13(a)) where dislocations could interact with each other.…”
Section: Dislocation Luminescence: a Tool To Probe Gettering At Dislosupporting
confidence: 54%
“…To date, no consensus has been reached as to the microscopic structure of the defects resulting in the D1 band luminescence. 12,13 Pizzini et al 12 have demonstrated that an oxygen precipitation anneal can also result in the formation of D1 centers. Further the energy of these peaks shift asymptotically with anneal duration from about 0.817 eV to the commonly reported value of 0.807 eV.…”
Section: Resultsmentioning
confidence: 99%
“…The origin of the D1 and D2 lines is still not understood. There are investigations referring that both lines are related to impurity atoms in the dislocation core (Higgs et al, 1993), dislocation jogs (Watson et al, 1998), or segments of dislocations (Lomer dislocations) appearing due to dislocation reactions, multi-vacancy and/or self-interstitial clusters trapped in the core (Jones et al, 2000).…”
Section: Electronic Properties Of Dislocations In Siliconmentioning
confidence: 99%